The Living Theatre and the French 1968 Revolution: Of Political and Theatrical Crises - Emeline JOUVE (E-REA)
In 1968, Jean Vilar invited the Living Theatre to the XXIIth edition of the Avignon Festival. This invitation of the American anarchist company was part of the new policy of Vilar who was eager to open his festival to the younger generation and to new theatrical forms. Yet, in the wake of the revolution of May in Paris, Vilar’s festival was debased as a “cultural supermarket” by Jean-Jacques Lebel and the enragés with whom the Living Theatre sympathized and a second revolution took place that summer 1968 in Avignon. The Odéon and Avignon crises of May and July, when theatres became the stages of spectacular heated debates about the creation of a new society, demonstrated the synergy between the political and the theatrical by simultaneously enhancing the theatricality of politics and the politics of theatre. Interestingly (and paradoxically), in spite of the importance of the part played by The Living Theatre in this French Revolution of 1968, official history has been oblivious of the involvement of the American company. This amnesia is symptomatic of the trauma of the lost utopian dreams which 1968 came to represent. The fifty anniversary of the revolution of 1968 is the occasion to lift the veil on the forgotten episodes of this historical moment, to turn back the clock and further discover about the participation of The Living Theatre.